Therapeutic Resistance to Anti-Hormonal Drugs in Breast Cancer - Hiscox, Stephen (Springer, 2017)
One of the main causes of failure in the treatment of breast cancer is the intrinsic presence of, or development of, drug resistance by the cancer cells. Recent studies on the mechanisms of cancer drug resistance have yielded important information highlighting both how tumour cells may escape these therapeutic constraints and that drug resistance may further impinge on tumour cell functions that may ultimately promote an adverse cell phenotype. New targets have been identified with potential therapeutic applications in resistant breast cancer leading to the subsequent evaluation of inhibitors of these targets in preclinical studies. Importantly, there is increasing evidence from such studies demonstrating the benefit of novel combination strategies as potential avenues for future drug regimens. Written by experts in the subject area, this book covers the molecular details and functional consequences of endocrine resistance in breast cancer with particular emphasis on the future applications of novel drug combinations that may be utilized to circumvent resistance and improve anti-tumour effects. This book represents a timely publication in the field of breast cancer research, providing current knowledge in the area of drug resistance and will be important reading material for clinicians and researchers alike.